Modelling and Seismic Response Analysis of Existing Italian Residential RC Buildings Retrofitted by Seismic Isolation. Issue 4 (12th March 2023) - Cardone, D.; Viggiani, L.R.S.; Perrone, G.; Telesca, A.; Di Cesare, A.; Ponzo, F.C.; Ragni, L.; Micozzi, F.; Dall'Asta, A.; Furinghetti, M.; Pavese, A.
ABSTRACT: The seismic performance of existing RC frame buildings seismically retrofitted by base isolation is examined. Two different types of isolation systems are considered, i.e.: rubber-based and friction-based isolation systems, respectively. Two different performance levels are examined, namely: Global collapse prevention and Usability preventing damage. Seismic performance is assessed by multi-stripe nonlinear time-history analysis, considering earthquake intensity levels with return period ranging from 10 to 100000 years. Results point out that seismic isolation works effectively in limiting damage well beyond the design limit state level while it shows a limited margin with respect to collapse beyond the design limit state level.